2004
DOI: 10.1080/10739680490449268
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine‐Induced Vasodilation and Reactive Hyperemia Are Not Affected by Acute Cyclo‐Oxygenase Inhibition in Human Skin

Abstract: These data give no support for a contribution of prostaglandins to acetylcholine-induced vasodilation or to reactive hyperemia in the skin microcirculation. In this vascular bed, local anesthesia seems to amplify acetylcholine-induced vasodilation via a prostaglandin-independent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
2
34
1
Order By: Relevance
“…These results contrast with those of Dalle-Ave et al (12) who found that neither cutaneous RH nor the cutaneous hyperemic response to acetylcholine depended on PGs. Results also contrast with those of Binggeli et al (3) who found that aspirin reduced rather than increased RH flow.…”
Section: Comparison With the Literaturecontrasting
confidence: 99%
See 2 more Smart Citations
“…These results contrast with those of Dalle-Ave et al (12) who found that neither cutaneous RH nor the cutaneous hyperemic response to acetylcholine depended on PGs. Results also contrast with those of Binggeli et al (3) who found that aspirin reduced rather than increased RH flow.…”
Section: Comparison With the Literaturecontrasting
confidence: 99%
“…For example, Wong et al (35) have shown that the duration of the falloff in flow of the cutaneous circulation is independent of NO synthase (NOS) inhibition, whereas Zhao et al (38) provided data that NO concentration measured by amperometric electrode did not change during RH. Also, the role of PGs in RH has been controversial (12,20). Thus whereas Larkin and Williams (20) studying laser-Doppler measurements of skin blood flow showed that RH in the human forearm is mediated by a local reflex involving sensory nerves and a cyclooxygenase (COX) product, showed that there was no significant response to acute systemic COX inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even more debatable remains the role of prostaglandins in the ACh-mediated response in human skin microcirculation. While some studies have confirmed their role (Durand et al, 2004;Holowatz et al, 2005, Kellogg et al, 2005Khan, 1997;Noon et al, 1998), others failed to do so (Abou-Elenin et al, 2002;Dalle-Ave et al, 2004;Morris& Shore, 1996).…”
Section: Human Skin Microcirculation and The Endothelium: Impact Of Nmentioning
confidence: 99%
“…Most studies using laser Doppler method in skin microcirculation attempt to determine the contribution of either NO or prostaglandins to the regulation of vascular tone and the results are inconsistent (Warren 1994;Noon et al 1998;BerghoV et al 2002;Dalle-Ave et al 2004).…”
Section: Introductionmentioning
confidence: 98%